Saksi sa kasaysayan - Barreiro, Roberto; Flores, Marissa; Sanchez, Leogarda (Quezon City GMA Network, 2001)
The story of the election and impeachment of President Joseph Ejercito Estrada, told in video news documentary. It shows the highlights of events, from the Senate Blue Ribbon Committee hearings, to the impeachment trial, and the days of People Power II. Saksi sa Kasaysayan is a presentation of the men and women of the GMA News and Public Affairs Division.
Part I. Erap sa harap ng pagsubok (55 mins.) -- Part 2. The president on trial (1 hr. 44 mins.) -- Part 3. People power II (1 hr. 8 mins.)
"Limited collector's edition"--container.
Dixie Alviz, Dodge Dillague, Jeannie Gualberto, Joel San Luis, directors.
Pt. 1 : Jessica Soho, host/writer.
Keywords: Philippine history